ASSESSMENT OF COMMERCIALIZATION OF PEARL MILLET AMONG FARMING HOUSEHOLDS IN SELECTED NORTHERN NIGERIA STATES - Sheu-Usman Oladipo Akanbi; Muhammed-Sanna Olanrewaju Moshood; Toyin B Ajibade; Adedayo Adekunle; Zainab Abdulrafiu (Agricultura)
This study assessed pearl millet commercialization among farming households in selected Northern Nigeria states. Multistage stratified random sampling procedure with replacement was employed to select 1,302 respondents for the study, the data was collected in 2020. Data analysis of this study was done using descriptive statistics, Household Commercialization Index (HCI), and Ordinary Least Square (OLS) regression. The result of the data analysis revealed that Pearl Millet commercialization was found to be low across the study area. Extension contact, years of farming experience, age of the respondent, total farm size, and distance to the market were the determinants of the level of commercialization across the Savannahs. Pearl millet commercialization to household income was 89.36% (0-50% Category), 4.26% (51-70% Category), 6.38% (71-100% Category). It is alarming that pearl millet, with all its advantages, is still being grown majorly on a subsistence basis throughout Northern Nigeria. Consequently, its commercialization, according to the findings of the research study, is low. It is therefore recommended that collective efforts should be made, and existing collaborations should be bettered to improve high yielding Pearl millet seed varieties. Farming households produce the crop majorly on a subsistent level.